Roles of Oral Bacteria in Cardiovascular Diseases - From Molecular Mechanisms to Clinical Cases: Porphyromonas gingivalis Is the Important Role of Intimal Hyperplasia in the Aorta - Kazuya Hokamura; Kazuo Umemura (Elsevier, 2010)
It has been reported that DNA of oral bacterial species, such as Porphyromonas gingivalis and Streptococcus mutans, was detected frequently in specimens of arteriosclerotic vessels. However, the source of DNA, whether from live intact bacteria or a part of the bacteria, has not been identified yet. Moreover, there was no precise evidence concerning involvement of oral bacteria in the progression of arteriosclerosis. We tried to clarify the involvement of P. gingivalis on the mechanisms of development of aortic intimal hyperplasia. Intravenous administration of P. gingivalis dramatically induced intimal hyperplasia in the mouse model with photochemical impairment of the femoral artery. However there were no changes identified in the mice without aortic impairment, even with the P. gingivalis infection. Concomitantly, S100 calcium-binding protein A9 (S100A9) and the embryonic isoform of myosin heavy chain (SMemb), a proliferative phenotypic marker of smooth muscle cells, were significantly overexpressed on the surfaces of smooth muscle cells present in the injured blood vessels. Similarly, increased expressions of S100A9 and SMemb proteins were observed in aneurismal specimens obtained from P. gingivalis - infected patients. We found that bacteremia induced by P. gingivalis leads to intimal hyperplasia associated with overexpressions of S100A9 and SMemb. Our results strongly suggest that oral-hematogenous spreading of P. gingivalis is a causative event in the development of aortic hyperplasia in periodontitis patients. Keywords:: periodontal pathogen, smooth muscle cell, atherosclerosis, aorta, oral bacteria